Global roles of currencies - Christian Thimann (European Central Bank (ECB), 2009)
This paper presents a new concept – the global roles of currencies. The concept combines the domestic and international (cross-border) use of currencies and therefore captures the overall importance of different currencies in a globalised economy. The measure of a currency's global role is based on the size and stage of development of the underlying economy, as well as the size and stage of development of its financial markets and the scope of financial instruments available in this currency. The paper applies the concept to 22 currencies of advanced and emerging economies. The results confirm the well-known ranking for the leading currencies – in particular the US dollar and the euro – but give considerably greater weight to currencies of emerging economies than the results obtained from the international debt market, which has so far been used as the basis for measuring the international role of currencies in capital markets. The paper also discusses this established measure in detail, arguing that in view of financial globalisation, an indicator based on currency shares in the international debt market alone represents a decreasing share of international financial market activity, as this market excludes government debt, other domestic debt and equities, which are in- creasingly of interest to international investors. The paper also presents an empirical application of the new global concept to examine cross-border portfolio holdings in debt and equity markets across advanced and emerging economies. It finds that the global role indicator is positively correlated with such holdings and, especially for emerging economies, fares better than the established international debt market indicator. The findings suggest a positive relationship between domestic financial development and international financial integration.
Keywords: F31; F33; F37; G15; E58; 330; global capital markets; international currencies; International Finance; Reservewährung; Währung; Währungssubstitution; Währungsreserven; Internationales Währungssystem